Age- and sex-specific differences in immune responses to BNT162b2 COVID-19 and live-attenuated influenza vaccines in UK adolescents - Jay, Cecilia; Adland, Emily; Csala, Anna; Lim, Nicholas; Longet, Stephanie; Ogbe, Ane; Ratcliff, Jeremy; Sampson, Oliver; Thompson, Craig P.; Turtle, Lance; Barnes, Eleanor; Dunachie, Susanna; et al. (Frontiers in Immunology, 2023)
Key to understanding COVID-19 correlates of protection is assessing vaccine-induced immunity in different demographic groups. Young people are at lower risk of COVID-19 mortality, females are at lower risk than males, and females often generate stronger immune responses to vaccination. We studied immune responses to two doses of BNT162b2 Pfizer COVID-19 vaccine in an adolescent cohort (n=34, ages 12-16), an age group previously shown to make significantly greater immune responses to the same vaccine compared to young adults. Adolescents were studied with the aim of comparing their response to BNT162b2 to that of adults, and to assess the impacts of other factors such as sex, ongoing SARS-CoV-2 infection in schools, and prior exposure to endemic coronaviruses that circulate at high levels in young people. At the same time, we were able to evaluate immune responses to the co-administered live attenuated influenza vaccine; trivalent inactivated flu vaccines have been shown to induce stronger immune responses in adult females. Blood samples from 34 adolescents taken pre- and post-vaccination with COVID-19 and influenza vaccines were assayed for SARS-CoV-2-specific IgG and neutralising antibodies, and cellular immunity specific for SARS-CoV-2 and endemic betacoronaviruses. IgG targeting influenza lineages contained in the influenza vaccine was also assessed. Robust neutralising responses were identified in previously-infected adolescents after one dose; two doses were required in infection-naïve adolescents. As previously demonstrated, total IgG responses to SARS-CoV-2 Spike were significantly higher among vaccinated adolescents compared to adults (aged 32-52) who received the BNT162b2 vaccine (comparing infection-naïve, 49,696 vs 33,339; p=0.03; comparing SARS-CoV-2 previously-infected, 743,691 vs 269,985; p<0.0001) by MSD v-plex assay. There was no evidence of stronger vaccine-induced immunity in females compared to males. These findings may result from the introduction of novel mRNA vaccination platforms, generating patterns of immunity divergent from established trends, and providing new insights into what might be protective following COVID-19 vaccination.